Enantioselective Box Behenken Optimized HPLC-DAD Method for the Simultaneous Estimation of Alogliptin Enantiomorphs in Pharmaceutical For mulations and their Pharmacokinetic Study in Rat Plasma - Ravi Kant; Ramesh Babu Bodla; Rubina Bhutani; Garima Kapoor (Tabriz University of Medical Sciences, 2019)
Purpose: A stereoselective high performance liquid chromatographic analytical method withphotodiode array detector was developed and validated as per the International Conferenceon Harmonization (ICH) guidelines for the determination of alogliptin (ALO) enantiomers informulations and rat plasma.Methods: Enantiomeric separation was performed on a Phenomenex Lux Cellulose-2 chiralcolumn. Box-Behnken design was used to identify the optimum conditions of the threeindependent variables for the desired output responses.Results: The HPLC peaks of ALO enantiomers and the internal standard pioglitazone wereachieved before 8 min with a resolution of 0.77 min between R and S enantiomer and resolutionof more than 2.0 between each enantiomer and pioglitazone (internal) with more than 95%recovery. The linearity range and the limit of quantification of both the enantiomers in rat plasmawere 10-70 ng mL-1 and 1.2 ng mL-1 respectively.Conclusion: The developed method after validation was successfully applied for estimation ofALO enantiomers in formulations. Single oral dose of 25 mg of the ALO racemate tablets wereadministered to a group of 6 healthy rats for a comparative pharmacokinetic study of both theenantiomers.